The role of nicotine, cotinine and caffeine on the electrochemical behavior and bacterial colonization to cp-Ti - Barão, Valentim A. R.; Ricomini-Filho, Antonio P.; Faverani, Leonardo P. [UNESP]; Del Bel Cury, Altair A.; Sukotjo, Cortino; Monteiro, Douglas R. [UNESP]; Yuan, Judy Chia-Chun; Mathew, Mathew T.; Amaral, Regiane C. do; Mesquita, Marcelo F.; Silva, Wander J. da; Assunção, Wirley G. [UNESP] (Elsevier B. V., 2015)
Although smoking promotes deleterious effect to bone healing, there is a lack of study investigating its role on the implant structure and biofilm growth. We hypothesized that nicotine, cotinine and caffeine would impair the corrosion resistance of commercially-pure titanium (cp-Ti) and would enhance Streptococcus sanguinis biofilm growth. Neither the smoking products nor the caffeine affected the corrosion tendency (P>.05) and the oxide layer resistance (P=.762) of cp-Ti. Lower capacitance values were noted in the presence of nicotine (P=.001) and cotinine (P=.0006). SEM showed no pitting corrosion, and the EDS spectra did not differ among groups. Nicotine (300μg/mL) induced higher surface roughness (P=.03) and greater surface change of cp-Ti. Nicotine at 3μg/mL, and cotinine at 0.3 and 3μg/mL increased the number of viable cells (P<.05). Biofilm exposed to nicotine (0.3, 3 and 30μg/mL) (P=.025, .030, .040, respectively) and cotinine (3 and 30μg/mL) (P=.027, .049, respectively) enhanced carbohydrate content. Biofilm biomass and protein content were similar among groups (P>.05). These findings suggest a greater biofilm accumulation in smokers, a risk factor that may lead to peri-implantitis.
Keywords: Biofilm; Caffeine; Corrosion; Cotinine; Dental implants; Electrochemistry; Nicotine